Influence of sowing time, environment and spacing on seed yield and oil recovery in camelina (Camelina sativa) - AGARWAL, ANKUR; ARYA, M C; AHMED, ZAKWAN (The Indian Journal of Agricultural Sciences, 2026)
An experiment was conducted to standardize the agro-technology of newly introduced crop camelina [Camelinasativa (L.) Crtz.] in India at DIBER field station, Pithoragarh. Four sowing times (October, November, December and January), two environment (open and polyhouse) and two line spacings (30 and 40 cm) along with broadcasting were used to study the effect on yield, yield attributing traits and oil content. The results revealed the significant effect of sowing time, environment and spacing on the seed yield of camelina. Results of this experiment revealed that October-November is the best month for sowing the crop with a seed yield of 13.68 –14.81 q/ha irrespective of the growing environment. Line spacing exhibited significantly higher seed yield (12.05-12.64 q/ha) over broadcasting (10.23 q/ha) with 30cm line spacing showing superiority over 40 cm.